2004
DOI: 10.1086/382194
|View full text |Cite
|
Sign up to set email alerts
|

The African Diaspora: Mitochondrial DNA and the Atlantic Slave Trade

Abstract: Between the 15th and 19th centuries ad, the Atlantic slave trade resulted in the forced movement of approximately 13 million people from Africa, mainly to the Americas. Only approximately 11 million survived the passage, and many more died in the early years of captivity. We have studied 481 mitochondrial DNAs (mtDNAs) of recent African ancestry in the Americas and in Eurasia, in an attempt to trace them back to particular regions of Africa. Our results show that mtDNAs in America and Eurasia can, in many case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
237
2
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(271 citation statements)
references
References 40 publications
25
237
2
7
Order By: Relevance
“…The mtDNAs were assigned to haplogroups L3b1a, L3d1b2, and L2a1f, respectively. Tracing these lineages to particular regions in Africa is challenging because of their pan-continental distribution, which is the result of thousands of years of population movements (e.g., the Bantu migrations) and continued gene flow (20)(21)(22). Nevertheless, we note that haplogroup L3b1a is one of the most common lineages found in the Lake Chad Basin (23).…”
Section: Significancementioning
confidence: 99%
“…The mtDNAs were assigned to haplogroups L3b1a, L3d1b2, and L2a1f, respectively. Tracing these lineages to particular regions in Africa is challenging because of their pan-continental distribution, which is the result of thousands of years of population movements (e.g., the Bantu migrations) and continued gene flow (20)(21)(22). Nevertheless, we note that haplogroup L3b1a is one of the most common lineages found in the Lake Chad Basin (23).…”
Section: Significancementioning
confidence: 99%
“…Nomenclature of African haplotypes follows Salas et al (2002Salas et al ( , 2004Salas et al ( ), with updates in Č erný et al (2007, Kivisild et al (2004), and Torroni et al (2006). For Native American haplogroups, we use the most updated nomenclature from Bandelt et al (2003) and Kong et al (2006), and for the European profiles, Achilli et al (2005Achilli et al ( , 2004, Loogväli et al (2004), and Sun et al (2006), among others.…”
Section: Databases and Statistical Analysismentioning
confidence: 99%
“…1 -4 It has been suggested that African mtDNAs appeared in Europe mostly as a result of the Atlantic slave trade beginning in seventeenth century, with Portugal being the destination point playing predominant role in further dispersal. 3 In addition, the medieval Arab/Berber conquest of Iberia might have also contributed to this process. 5,6 As for eastern Europe, it seems that only African children's traffic from Turkey to Russia at the end of seventeenth century might have played the leading role in African slave trade.…”
Section: Introductionmentioning
confidence: 99%